Manufacturing process of particle intermetallic compound reinforced Al base composites by infiltration-reaction method - Yongbum CHOI (The Japan Society of Mechanical Engineers, 2016)
A new process is proposed to fabricate an aluminum alloy matrix composite dispersed with intermetallic compound particles by using the reaction between porous nickel and molten aluminum alloy. The intermetallic compound particles reinforced aluminum alloy matrix composite was manufactured with the infiltration-reaction method. Four different specific surface areas of porous nickel were used to fabricate the composites and then the porosity inside composites were investigated. Porous nickel reacted with molten aluminum alloy at 973 K, and the intermetallic compound, Al3Ni was generated on the surface of the porous nickel. The generated intermetallic compound Al3Ni, was delaminated according to the difference of thermal expiation coefficient with nickel. And the intermetallic compounds moves in the direction of aluminum matrix. The area fraction of the intermetallic compounds increased with the increasing specific surface area of porous nickel. In addition, the hardness of composite increased by the increasing specific surface area of porous nickel.